The extent to which the faculty at Al-Mustansiriya University uses electronic resources provided by the central library of the university (Journal of the College of Basic Education, 2022)
The study deals with the extent to which faculty members at Al-Mustansiriya University use electronic resources provided by the central library of the university, by identifying the extent of their knowledge of their availability in the library, the reality of use and its purposes, the importance of its availability in the library from their point of view, the extent to which it meets the purposes of their use, and the extent of their ability to search it. And to highlight the obstacles that prevent or reduce their benefit from them.